Aplikasi Biochar dengan Pupuk Kandang Terhadap Pertumbuhan dan Produksi Kacang Tanah (Arachis hypogaea L.) - Fadhlina, Fadhlina; Jamidi, Jamidi; Usnawiyah, Usnawiyah (Faculty of Agriculture, Universitas Malikussaleh, 2017)
The main aim of this study is to investigate the effect of the use of biochar and cow manure and their interaction with peanut production and growth. This research was conducted in Reuleut Barat Village, Muara Batu Sub-district, North Aceh Regency which conducted from April to September 2015. This research used Factorial Randomized Block Design with 3 replications. Two factors studied: biochar (B) and manure cow (K), each consisting of B0 (without biochar), B1 (biochar 5 tons / ha) and K0 (without manure), K1 (manure 5 tons / ha), K2 (manure 10 tons / ha). The results showed that the use of biochar (B) had no significant effect on plant height, stem diameter, number of leaves, number of branches, amount of ginofor, weight of pod per plant, dry weight of 100 seeds and dry weight of seed per plot. But it gives a significant influence on the root length. Furthermore, the application of cow manure (K) has a very significant effect on plant height at age 15 days after planting. There is interaction to plant height at 15 days after planting and plant height at 30 days after planting. The application of biochar gave an effect significantly on the growth of peanut crops and the application of cow manure also affected the growth of peanut crops. There is an interaction between the application of biochar and cow manure to the growth of peanut crops